Keberkesanan teaching games for understanding (TGfU) melalui permainan tradisional terhadap kecergasan fizikal, emosi dan keseronokan dalam kalangan murid ponteng di sekolah rendah - Ibrahim, Mohamad Fadil (2022)
A quality learning process is able to increase students' experience in positive attitude, emotional and enjoyment. The conceptual integration of TGfU teaching modules through traditional games is seen to be able to change teaching and learning to be more structured, effective, and interesting. The cross-sectional and quasiexperimental is used in this study. In the phase one study, the evaluation of the modules by experts showed that the constructed modules were very suitable For Study 1, the module was evaluated by experts which indicated that the module is suitable to be applied to the primary students, The result showed that the module has the level of usability of the module (95.4%), lesson planning (91.0%), module content (97.7%), TnL activities (99.0%), and related aspects of language (100%) agree and strongly agree. For Study 2, the confirmatory factor analysis (CFA) test of the AEQ-PE-M questionnaire showed the model fit the data well with acceptable fit indices (CFI = 0.936, TLI = 0.926, RMSEA = 0.039 (90% CI, 0.034, 0.045), SRMR = 0.049). The final model of the Q-LES-Q-M also showed acceptable construct validity by using CFA (CFI = 0.930, TLI = 0.926, RMSEA = 0.029 (90% CI, 0.025, 0.032), SRMR = 0.042)). In addition, the Composite Reliability (CR) and Cronbach’s Alpha (CA), indicated satisfactory reliability of AEQ-PE-M and Q-LES-Q-M. In study 3, mixed factorial ANOVA was used to test effectiveness of the TGfU module in traditional games between the intervention and control groups. The result showed that for physical aspects, there was no significant effect in time, F (1,58) = 7.559, p-value = 0.080, eta2 = 0.115 and in group, F (1,58) = 0.036, p = 0.850, eta2 = 0.001. However, there is a significant interaction effect with time and groups, F (1,58) = 11.077, with p = 0.020, eta2 = 0.160. In terms of emotion aspect, there was also no significant effect in time, F (1,58) = 0.278, p = 0.600, eta2 = 0.005 and in group, F (1,58) = 1.038, p-value = 0.312, eta2 = 0.018. But, the interaction effect was significant, F (1,58) = 0.006, p = 0.937, eta2 = 0.001. As for enjoyment aspect, the results showed a significant time effect, F (1,58) = 70.087, p = 0.001, eta2 = 0.547 and group effect, F (1,58) = 3.703, p = 0.001, eta2 = 0.499. However, there was no significant interaction effect, F (1,58) = 57.672, p = 0.590, eta2 = 0.060. Further analysis by using t-test was conducted to examine the mean differences in levels of physical fitness, emotional, and enjoyment before and after the intervention for treatment group. Results showed a significant difference in mean score of the physical test (SEGAK) for the treatment group t (29) = -3.751, p < 0.001. For emotions, there was no significant difference found in mean score with t (119) = 4.140, p < 0.742. In term of enjoyment, there was a significant mean score difference on the pleasure test with t (29) = 8.580, p < 0.001. Furthermore, a correlation test was conducted between physical, emotional, and enjoyment. Only the physical constructenjoyment showed a positive relationship, with p-value = 0.409 (0.250), physicalemotional with p-value = -0.56 (0.768) and emotional construct-pleasure = -0.269 (0.166) indicates an insignificant value. The intervention program through the TGfU concept teaching module on truant students showed that it is an effective intervention to improve the physical aspects and enjoyment besides creating a positive relationship between physical fitness and emotional among truant students in primary school.